Sleep quality associated with mood in elite athletes - Andrade, A.; Bevilacqua, G.; Casagrande, P.; Brandt, R.; Coimbra, D. (The Physician and Sportsmedicine, 2019)
Objectives: This study aimed to analyze the association between sleep quality and mood in elite athletes of different competitive levels.